Evaluation of rigid pavement damage using PCI and bina marga approaches (case study: Saketi–Malingping road, KM 17–27) - Irwan; Muhammad Oka Mahendra (Journal of Infrastructure Planning and Engineering, 2026)
This study aims to evaluate the damage condition of the Saketi - Malingping road section (KM 17-KM 27) using two assessment approaches: the Pavement Condition Index (PCI) and the Bina Marga method. This road section is a strategic arterial road in Pandeglang Regency, Banten, which experiences high operational pressure and shows signs of surface distress. Data were collected through field surveys across 42 segments. The PCI analysis results show an average value of 99.99, indicating the road is in a "Very Good" category structurally. Assessment using the Bina Marga method revealed that block cracking is the most dominant type of damage, accounting for approximately 89.31% of the total damaged area. Although the overall road condition value is still considered good, the presence of extensive block cracking indicates early signs of structural vulnerability. The study recommends preventive measures such as crack sealing, localized overlay, or reconstruction of severely cracked sections.